Why the Mars probe [accident investigation]. - Oberg, J. (IEEE spectrum)
On 23 September, through a series of still-baffling errors, flight controllers at the Jet Propulsion Laboratory, a California Institute of Technology facility under contract to NASA, sent erroneous steering commands to the Mars Climate Observer as it neared the target planet. Obeying blindly like all true robots, the probe, metaphorically speaking, marched off the cliff and was destroyed. NASA assigned three separate teams to investigate the embarrassing, US 125 million dollars debacle and determine its cause. Preliminary public statements faulted a slip-up between the probe's builders and its operators, a failure to convert the English units of measurement used in construction into the metric units used for operation. After six weeks, on 10 November, NASA officials released their preliminary findings. This paper describes an IEEE Spectrum investigation which had been going on separately, using unofficial sources associated with the program and independent experts. Spectrum quickly learned that far more had gone wrong than just a units conversion error. A critical flaw was a program management grown too confident and too careless, even to the point of missing opportunities to avoid the disaster